(3YjhH GdfaSs - (3GdSdej , eMeO Hf GdMSjf Hf eMeO Hf ehSi GdGROj GdSdej GdfjSGHhQj, CHh YHO GdQMef,J (B412 (3g` s
(3ChdgG (B:s
(3CNHQfG GdTjN GdUGdM CHh GdMSf Ydi Hf CHj YHO Gddg Hf CHj GdMSf Hf GdebO GdHZOGOi bGd Gddg JHGQc hJYGdi (B( (3Ef GdfaS dCeGQI HGdShA (B) (3hbGd (B: ( (3hfgi GdfaS Yf Gdghi (B) (3hZjQgG ef GdBjGJ s
(3BNQgG (B:s
(3hGddg JYGdi jhabfG deJGHYI GdQTO ajRjd YfG ehGQO GdZadI hGdTghGJ hjLYdfG ai cfag hMjGWJg hYUeJg hQYGjJg aEfg GdbGOQ Ydi Pdc hGdhGgH dg Je cJGH YjhH GdfaS hddg GdMeO s
(3GdfSNI HgG MhGTs
(3HChdg hBNQg bQGAGJs
(3HBNQg JUMjMGJs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs